Hepatocellular carcinoma in a free‐living marmoset (Callithrix sp.) with concomitant biliary trematodiasis. Issue 2 (28th December 2017) - Díaz‐Delgado, J.; Sanches, T. C.; dos Santos‐Cirqueira, C.; Coimbra, A. A. C.; Guerra, J. M.; Joppert, A.; Di Loretto, C.; Rizardi, M. B.; Sansone, M.; Nagamori, F. O.; Gonçalves, P. S.; Ressio, R.; et al.
Abstract: Hepatocellular carcinoma (HCC) is rare in New World primates. We report the gross, microscopical, and immunocytochemical features of a spontaneous HCC in a free‐living marmoset ( Callithrix sp.). Hepatitis B and C virus and aflatoxin immunohistochemistry were negative; however, concomitant intra‐ and extrahepatic biliary trematodiasis could have played a role.